Battery and electric device

By using composite heat insulation pads in the battery, including the first heat insulation layer, the composite phase change layer and the second heat insulation layer, the problem of thermal runaway in the battery is solved, and better thermal insulation performance and battery safety are achieved.

CN222581295UActive Publication Date: 2025-03-07CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202420290160.3
Authority / Receiving Office
CN · China
Patent Type
Utility models(China)
Current Assignee / Owner
Filing Date
2024-02-08
Publication Date
2025-03-07
Estimated Expiration
2034-02-08

AI Technical Summary

Technical Problem

Existing batteries can easily cause heat diffusion of the entire battery after thermal runaway, resulting in serious damage. How to prevent and alleviate the thermal runaway of the battery is an urgent problem.

Method used

A battery is designed, using a composite heat insulation pad, including a laminated first heat insulation layer, a composite phase change layer and a second heat insulation layer, and a phase change material layer and a packaging layer are arranged in the composite phase change layer to absorb heat and prevent heat loss through this structure.

Benefits of technology

It effectively improves the thermal insulation performance of the battery, slows down heat out of control, and reduces the risk and degree of battery damage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN222581295U_ABST
    Figure CN222581295U_ABST
Patent Text Reader

Abstract

The utility model relates to a battery and an electric device. The battery comprises a single battery body and a composite heat insulation pad arranged on at least one side of the single battery body, the composite heat insulation pad comprises a first heat insulation layer, a composite phase change layer and a second heat insulation layer which are arranged in a stacked mode, and the composite phase change layer comprises a phase change material layer and a packaging layer arranged on the peripheral side of the phase change material layer. The thickness of the composite phase change layer ranges from 1 mm to 4 mm, and the thickness of the first heat insulation layer and the thickness of the second heat insulation layer range from 1 mm to 3 mm independently. The laminated arrangement structure and the thickness of the first heat insulation layer, the composite phase change layer and the second heat insulation layer of the composite heat insulation pad are optimized, so that a better heat insulation effect is obtained, and the battery applying the composite heat insulation pad has a good thermal runaway resistance and slowing effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a battery and an electrical device. Background Art

[0002] With the rapid development of new energy technologies, batteries are being used more and more widely in many fields, and people are demanding higher and higher performance from batteries, such as higher and higher requirements for battery energy density.

[0003] However, battery cells with higher energy density have large residual energy after thermal runaway. When one of the battery cells thermally runs away, its heat will continue to transfer from one battery cell to the adjacent battery cell, thus causing heat diffusion of the entire battery and causing serious damage to the entire battery. Therefore, how to slow down battery thermal runaway is an urgent problem to be solved. Utility Model Content

[0004] Based on this, it is necessary to provide a battery and an electrical device to mitigate the problem of thermal runaway of the battery.

[0005] In a first aspect, the present application provides a battery, comprising a battery cell and a composite thermal insulation pad arranged on at least one side of the battery cell, the composite thermal insulation pad comprising a first thermal insulation layer, a composite phase change layer, and a second thermal insulation layer which are stacked, the composite phase change layer comprising a phase change material layer and a packaging layer arranged on the outer peripheral side of the phase change material layer, the thickness of the composite phase change layer is 1 mm to 4 mm, and the thickness of the first thermal insulation layer and the second thermal insulation layer are each independently 1 mm to 3 mm.

[0006] The above-mentioned battery with a composite thermal insulation pad, wherein the composite thermal insulation pad is provided with a first thermal insulation layer and a second thermal insulation layer at the same time, can play a good thermal insulation role; on the other hand, the composite phase change layer arranged between the first thermal insulation layer and the second thermal insulation layer can absorb the heat transferred from the thermal insulation layers on both sides, so that the thermal insulation performance of the composite thermal insulation pad can be further improved. The phase change material layer is arranged in the packaging layer, so that the phase change material layer in the composite phase change layer is physically isolated from the thermal insulation layer on the outside, and then before the packaging layer fails, the phase change material will not diffuse into the thermal insulation layer to form a heat conduction path, and then will not change the structure of the thermal insulation layer and its thermal insulation performance; at the same time, the thickness of the first thermal insulation layer, the second thermal insulation layer and the composite phase change layer of the composite thermal insulation pad are optimized, so that the above-mentioned composite thermal insulation pad can obtain better thermal insulation performance at a lower thickness. The battery with the composite thermal insulation pad has a good effect of slowing down the thermal runaway of the battery.

[0007] In some embodiments, the battery satisfies at least one of the following conditions:

[0008] (1) The thickness of the composite phase change layer is 1.5 mm to 3.5 mm;

[0009] (2) The thickness of the first heat-insulating layer and the second heat-insulating layer are each independently 1 mm to 2.5 mm.

[0010] In some of the embodiments, the battery cell is a ternary lithium battery, the thickness of the composite phase change layer is 1.5 mm to 3.3 mm, and the thickness of the first thermal insulation layer and the second thermal insulation layer are each independently 1 mm to 2.5 mm.

[0011] In some of the embodiments, the atomic ratio of nickel element in the ternary positive electrode material of the battery cell is greater than 0 and less than 50% of the ternary elements, and the thickness of the first thermal insulation layer and the second thermal insulation layer are independently 1 mm to 2 mm.

[0012] In some embodiments, the battery satisfies one of the following conditions:

[0013] (1) The capacity of the battery cell is less than 120 Ah, the thickness of the composite phase change layer is 1.5 mm, and the thickness of the first thermal insulation layer and the second thermal insulation layer are independently 1 mm to 1.5 mm;

[0014] (2) The capacity of the battery cell is ≥120Ah and <215Ah, the thickness of the composite phase change layer is 2.3mm, and the thickness of the first thermal insulation layer and the second thermal insulation layer are independently 1.5mm to 2mm;

[0015] (3) The capacity of the battery cell is ≥215Ah and <260Ah, the thickness of the composite phase change layer is 3.3mm, and the thickness of the first thermal insulation layer and the second thermal insulation layer are independently 1.5mm to 2mm.

[0016] In some of the embodiments, the nickel element in the ternary positive electrode material in the battery cell accounts for ≥50% and <70% of the atoms of the ternary elements, the thickness of the composite phase change layer is 2.3mm~3.3mm, and the thickness of the first thermal insulation layer and the second thermal insulation layer are each independently 1.5mm~2mm.

[0017] In some embodiments, the battery satisfies one of the following conditions:

[0018] (1) The capacity of the battery cell is less than 150 Ah, and the thickness of the first thermal insulation layer and the second thermal insulation layer are each independently 1.5 mm;

[0019] (2) The capacity of the battery cell is ≥150Ah and <200Ah, the thickness of the composite phase change layer is 3.3mm, and the thickness of the first thermal insulation layer and the second thermal insulation layer are independently 1.5mm to 2mm;

[0020] (3) The capacity of the battery cell is ≥200 Ah and <260 Ah, and the thickness of the first thermal insulation layer and the second thermal insulation layer are independently 1.5 mm to 2 mm.

[0021] In some of the embodiments, the nickel element in the ternary positive electrode material in the battery cell accounts for ≥ 70% of the atoms of the ternary elements.

[0022] In some embodiments, the battery satisfies one of the following conditions:

[0023] (1) The capacity of the battery cell is less than 100 Ah, the thickness of the composite phase change layer is 1.5 mm, and the thickness of the first thermal insulation layer and the second thermal insulation layer are independently 1 mm to 1.5 mm;

[0024] (2) The capacity of the battery cell is ≥100Ah and <120Ah, the thickness of the composite phase change layer is 2.3mm-3.3mm, and the thickness of the first thermal insulation layer and the second thermal insulation layer are each independently 1mm-1.5mm;

[0025] (3) The capacity of the battery cell is ≥120 Ah, the thickness of the composite phase change layer is 2.3 mm to 3.3 mm, and the thickness of the first thermal insulation layer and the second thermal insulation layer are each independently 2 mm to 2.5 mm.

[0026] In some embodiments, the battery cell is a lithium iron phosphate battery, the thickness of the composite phase change layer is 1.5 mm to 3.3 mm, and the thickness of the first thermal insulation layer and the second thermal insulation layer are each independently 1 mm to 2 mm.

[0027] In some embodiments, the battery satisfies one of the following conditions:

[0028] (1) The capacity of the battery cell is less than 160 Ah, the thickness of the composite phase change layer is 1.5 mm, and the thickness of the first thermal insulation layer and the second thermal insulation layer are independently 1 mm to 1.5 mm;

[0029] (2) The capacity of the battery cell is ≥160Ah and <260Ah, the thickness of the composite phase change layer is 1.5 mm to 2.3 mm, and the thickness of the first thermal insulation layer and the second thermal insulation layer are each independently 1 mm to 1.5 mm;

[0030] (3) The capacity of the battery cell is ≥260Ah and <450Ah, the thickness of the composite phase change layer is 2.3 mm to 3.3 mm, and the thickness of the first thermal insulation layer and the second thermal insulation layer are each independently 1.5 mm to 2 mm.

[0031] In some embodiments, the battery cell is a sodium ion battery, the thickness of the composite phase change layer is 1.5 mm to 2.3 mm, and the thickness of the first thermal insulation layer and the second thermal insulation layer are each independently 1 mm to 2 mm.

[0032] In some embodiments, the battery satisfies one of the following conditions:

[0033] (1) The capacity of the battery cell is less than 93 Ah, the thickness of the composite phase change layer is 1.5 mm, and the thickness of the first thermal insulation layer and the second thermal insulation layer are independently 1 mm to 1.5 mm;

[0034] (2) The capacity of the battery cell is ≥93Ah and <117Ah, and the thickness of the first thermal insulation layer and the second thermal insulation layer are independently 1 mm to 1.5 mm;

[0035] (3) The capacity of the battery cell is ≥117Ah and <180Ah, the thickness of the composite phase change layer is 1.5mm, and the thickness of the first thermal insulation layer and the second thermal insulation layer are independently 1.5mm to 2mm.

[0036] In some embodiments, there are multiple battery cells, and the composite thermal insulation pad is disposed between at least two adjacent battery cells.

[0037] In some of the embodiments, the composite thermal insulation pad is disposed between the large surfaces of two adjacent battery cells.

[0038] In some embodiments, edges of the first thermal insulation layer and the second thermal insulation layer are connected to each other to form an assembly cavity, and the composite phase change layer is located in the assembly cavity.

[0039] In some embodiments, an edge of at least one side surface of at least one of the first thermal insulation layer and the second thermal insulation layer forms a convex portion, and the convex portion encloses at least a portion of the assembly cavity.

[0040] In some embodiments, the composite thermal insulation pad also includes a first packaging frame and a second packaging frame, the first packaging frame is arranged on one side of the first thermal insulation layer, and the second packaging frame is arranged on one side of the second thermal insulation layer, and the first packaging frame and the second packaging frame cooperate to fix the first thermal insulation layer, the composite phase change layer and the second thermal insulation layer.

[0041] In some embodiments, the first packaging frame has a first limiting groove, the second packaging frame has a second limiting groove, and the first thermal insulation layer, the composite phase change layer and the second thermal insulation layer are limited in a limiting space formed by the first limiting groove and the second limiting groove.

[0042] In some embodiments, the composite thermal insulation pad satisfies at least one of the following conditions:

[0043] (1) The composite thermal insulation pad further comprises a first adhesive layer and a second adhesive layer, wherein the first thermal insulation layer is connected to the encapsulation layer via the first adhesive layer, and the second thermal insulation layer is connected to the encapsulation layer via the second adhesive layer;

[0044] (2) The composite thermal insulation pad further includes a release adhesive layer, the release adhesive layer includes a third adhesive layer and a release film, the third adhesive layer is arranged on the outer surface of the first thermal insulation layer and the second thermal insulation layer, and the release film is arranged on the outer surface of the third adhesive layer;

[0045] (3) The first thermal insulation layer and the second thermal insulation layer are ceramic material layers;

[0046] (4) The encapsulation layer is an aluminum-plastic film or a polymer encapsulation film;

[0047] (5) The thickness of the packaging layer is 0.1 mm to 0.3 mm.

[0048] In some embodiments, the battery cell includes a housing; the housing satisfies at least one of the following features:

[0049] (1) The wall thickness of the shell is 0.5 mm to 0.8 mm;

[0050] (2) The housing is a rectangular housing;

[0051] (3) The shell is an aluminum alloy shell.

[0052] In some embodiments, the battery cell includes a shell, which is a rectangular shell, has an opening, the opening direction of the shell is the height direction of the shell, the height of the shell is 80mm~210mm, the length of the shell is 90mm~240mm, and the width of the shell is 20mm~80mm.

[0053] In a second aspect of the present application, an electrical device is provided, comprising any of the batteries described above. BRIEF DESCRIPTION OF THE DRAWINGS

[0054] Figure 1 A schematic diagram of the structure of a battery according to one embodiment of the present application;

[0055] Figure 2 This is a schematic diagram of the exploded structure of a battery according to one embodiment of the present application;

[0056] Figure 3 This is a schematic diagram of the cross-sectional structure of a composite thermal insulation pad according to one embodiment of the present application;

[0057] Figure 4 This is a schematic diagram of the cross-sectional structure of a composite thermal insulation pad according to another embodiment of the present application;

[0058] Figure 5 This is a schematic diagram of the cross-sectional structure of a composite thermal insulation pad according to another embodiment of the present application;

[0059] Figure 6 This is a schematic diagram of the cross-sectional structure of a composite thermal insulation pad according to another embodiment of the present application;

[0060] Figure 7 This is a schematic diagram of the three-dimensional structure of a composite thermal insulation pad according to another embodiment of the present application;

[0061] Figure 8 for Figure 7 A schematic cross-sectional view of the composite thermal insulation pad shown in FIG.

[0062] Fig. 9 for Figure 8 An exploded cross-sectional view of the composite thermal insulation pad shown;

[0063] Fig.10 This is a schematic diagram of the cross-sectional structure of a composite thermal insulation pad according to another embodiment of the present application;

[0064] Fig.11 is a schematic structural diagram of a battery cell in a battery according to an embodiment;

[0065] Fig.12 A schematic diagram of an electrical device using a battery as a power source according to an embodiment of the present application;

[0066] Fig.13 The actual measured curve of the thermal insulation performance of the battery 2 in Example 1 and the simulation test curve using the heat estimation model;

[0067] Fig.14 The actual measured curve of the thermal insulation performance of the battery 3 in Example 1 and the simulation test curve using the heat estimation model;

[0068] Fig.15 A schematic diagram of a test method in one embodiment;

[0069] Fig.16 FIG. 4 is a diagram showing the internal structure of a computer device in one embodiment.

[0070] Description of reference numerals:

[0071] 10. Composite thermal insulation pad; 11. First thermal insulation layer; 12. Second thermal insulation layer; 13. Composite phase change layer; 131. Phase change material layer; 132. Packaging layer; 1321. Packaging margin; 141. First packaging frame; 142. Second packaging frame; 151. First adhesive layer; 152. Second adhesive layer; 16. Third thermal insulation layer;

[0072] 20. Battery cell; 21. Housing; 22. Electrode assembly; 23. Cover plate;

[0073] 30. Battery;

[0074] 40. Electrical equipment. DETAILED DESCRIPTION

[0075] In order to make the above-mentioned purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are described in detail below in conjunction with the accompanying drawings. In the following description, many specific details are set forth to facilitate a full understanding of the present application. However, the present application can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present application, so the present application is not limited by the specific embodiments disclosed below.

[0076] In the description of the present application, it should be understood that if the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential", etc. appear, the orientation or position relationship indicated by these terms is based on the orientation or position relationship shown in the accompanying drawings, which is only for the convenience of describing the present application and simplifying the description, and does not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present application.

[0077] In addition, if the terms "first" or "second" appear, these terms are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include at least one of the features. In the description of this application, if the term "plurality" appears, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

[0078] In the present application, unless otherwise clearly specified and limited, if there is a description that a first feature is "above" or "below" a second feature, etc., or similar descriptions appear, it may mean that the first and second features are in direct contact, or that the first and second features are in indirect contact through an intermediate medium. Moreover, the first feature being "above", "above" and "above" the second feature may mean that the first feature is directly above or obliquely above the second feature, or simply means that the first feature is higher in level than the second feature. The first feature being "below", "below" and "below" the second feature may mean that the first feature is directly below or obliquely below the second feature, or simply means that the first feature is lower in level than the second feature.

[0079] It should be noted that if an element is referred to as being "fixed to" or "disposed on" another element, it may be directly on the other element or there may be a central element. If an element is considered to be "connected to" another element, it may be directly connected to the other element or there may be a central element at the same time. If any, the terms "vertical", "horizontal", "upper", "lower", "left", "right" and similar expressions used in this application are for illustrative purposes only and do not represent the only implementation method.

[0080] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0081] At present, judging from the development of the market situation, the application of batteries is becoming more and more extensive. Batteries, especially power batteries, are not only used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, but are also widely used in electric vehicles such as electric bicycles, electric motorcycles, electric cars and other fields. With the continuous expansion of the application field of power batteries, the market demand is also constantly expanding.

[0082] A battery cell is the smallest unit that makes up a battery. A battery may include one or more battery cells, and multiple battery cells may be connected in series, in parallel, or in a hybrid connection. Among them, a hybrid connection means that multiple battery cells are connected in both series and in parallel.

[0083] After multiple battery cells are connected to each other and arranged in a certain order, they can be directly placed in a box to assemble into a battery. Alternatively, multiple battery cells can be first assembled into a battery module, and then multiple battery modules are connected to each other to form a whole, and finally the whole battery module is placed in a box to form a battery.

[0084] In order to solve the above-mentioned battery thermal runaway problem and reduce the degree of damage and risk to the entire battery, the present application provides a battery with a composite thermal insulation pad, and optimizes the film thickness of the composite thermal insulation pad to obtain a better thermal insulation effect. Furthermore, the present application optimizes the film thickness of the composite thermal insulation pad based on the different systems of the battery cells and the different capacities of the battery cells, thereby obtaining a better thermal insulation effect.

[0085] See also Figure 1 and Figure 2 In one embodiment of the present application, a battery 30 is provided, including a battery cell 20 and a composite thermal insulation pad 10 disposed on at least one side of the battery cell 20 .

[0086] See also Figure 3 The composite thermal insulation pad 10 includes a first thermal insulation layer 11, a composite phase change layer 13, and a second thermal insulation layer 12 which are stacked. The composite phase change layer 13 includes a phase change material layer 131 and an encapsulation layer 132 arranged on the outer peripheral side of the phase change material layer 131. The thickness of the composite phase change layer 13 is 1 mm to 4 mm, and the thickness of the first thermal insulation layer 11 and the second thermal insulation layer 12 are each independently 1 mm to 3 mm.

[0087] The battery 30 using the composite thermal insulation pad 10 is provided with a first thermal insulation layer 11 and a second thermal insulation layer 12, which can play a good role in thermal insulation. On the other hand, the composite phase change layer 13 disposed between the first thermal insulation layer 11 and the second thermal insulation layer 12 can absorb the heat transferred from the thermal insulation layers on both sides, so that the thermal insulation performance of the composite thermal insulation pad 10 can be further improved. The phase change material layer 131 is disposed in the encapsulation layer 132, so that the phase change material layer 131 in the composite phase change layer 13 is physically isolated from the thermal insulation layer on the outside, and then before the encapsulation layer 132 fails, the phase change material will not diffuse into the thermal insulation layer to form a heat conduction path, and then will not change the structure of the thermal insulation layer and its thermal insulation performance, so that the composite thermal insulation pad 10 has good thermal insulation performance. At the same time, the thickness of the first thermal insulation layer 11, the second thermal insulation layer 12 and the composite phase change layer 13 of the composite thermal insulation pad 10 is optimized, so that the composite thermal insulation pad 10 can obtain a better thermal insulation effect at a lower thickness. The battery using the composite thermal insulation pad 10 has a good effect of slowing down the thermal runaway of the battery.

[0088] The battery 30 using the above-mentioned composite thermal insulation pad 10, when the battery 30 is in normal working state, mainly uses the first thermal insulation layer 11 and the second thermal insulation layer 12 located on the outside to play a thermal insulation role; when the battery 30 heats up abnormally and a large amount of heat is transferred to the phase change material layer 131 in the composite phase change layer 13, the phase change material layer 131 can absorb a large amount of heat and then undergo a phase change; when the phase change material layer 131 continues to absorb heat, the phase change material therein is converted into a gaseous state and breaks through the packaging layer 132, discharging the high-temperature gas and causing the packaging of the packaging layer 132 to fail, at which time the first thermal insulation layer 11 and the second thermal insulation layer 12 continue to play a thermal insulation role.

[0089] In this application, unless otherwise specified, "battery cell" refers to a basic unit that can realize the mutual conversion of chemical energy and electrical energy, and further, generally speaking, at least includes a positive electrode sheet, a negative electrode sheet and an electrolyte. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting active ions between the positive electrode sheet and the negative electrode sheet.

[0090] As an example, the thickness of the composite phase change layer 13 can be 1mm, 1.5mm, 2mm, 2.3mm, 2.5mm, 3mm, 3.5mm. It can be understood that the thickness of the composite phase change layer 13 refers to the sum of the thickness of the encapsulation layer 132 on both sides and the thickness of the phase change material layer 131 in the film layer stacking direction of the composite thermal insulation pad 10, that is, the thickness direction. In some embodiments, the thickness can also be a range consisting of any two of the above point values ​​as end values, similar to the following, for example, 1.5mm to 3.5mm.

[0091] As an example, the thickness of the first heat insulation layer 11 and the second heat insulation layer 12 are independently 1 mm, 1.5 mm, 2 mm, 2.3 mm, and 2.5 mm. In some embodiments, the thickness may also be 1 mm to 2.5 mm.

[0092] Furthermore, the present application optimizes the film thickness of the composite thermal insulation pad 10 based on the different systems of the battery cells 20, thereby obtaining a better thermal insulation effect. The battery cell 20 system includes a ternary lithium battery (referred to as ternary in Table 1), a lithium iron phosphate battery (LFP battery) and a sodium ion battery (sodium battery). The details are shown in Table 1 below.

[0093] Table 1

[0094]

[0095]

[0096] Please refer to Table 1. In some embodiments, the battery cell 20 is a ternary lithium battery, the thickness of the composite phase change layer 13 is 1.5 mm to 3.3 mm, and the thickness of the first insulation layer 11 and the second insulation layer 12 are each independently 1 mm to 2.5 mm.

[0097] Based on the different nickel content in the ternary positive electrode materials, the ternary lithium battery further optimizes the film thickness of the composite thermal insulation pad 10 to obtain a better thermal insulation effect. It can be understood that the Ni content in the ternary positive electrode material in Table 1 refers to the atomic ratio of nickel element to ternary elements. 811 Taking the ternary positive electrode material as an example, its nickel content refers to the atomic ratio of nickel element in the ternary elements of nickel, cobalt and manganese, which is 80%.

[0098] The ternary positive electrode material in the present application contains nickel, which includes but is not limited to at least one of lithium nickel cobalt manganese oxide (hereinafter referred to as "NCM") or lithium nickel cobalt aluminum oxide (hereinafter referred to as "NCA"). Non-limiting examples of lithium nickel cobalt manganese oxide (NCM) may include LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ) etc. Non-limiting examples of lithium nickel cobalt aluminum oxide (NCA) may include LiNi 0.8 Co 0.15 Al 0.05 O2.

[0099] In some of the embodiments, the atomic ratio of nickel element in the ternary elements of the ternary positive electrode material in the battery cell 20 is greater than 0 and less than 50%, and the ternary positive electrode material is generally considered to be a low-nickel ternary system; the thickness of the composite phase change layer 13 is 1.5 mm to 3.3 mm, and the thickness of the first thermal insulation layer 11 and the second thermal insulation layer 12 are each independently 1 mm to 2 mm.

[0100] Furthermore, in the case of the same battery cell 20 system, the present application optimizes the film thickness of the composite thermal insulation pad 10 based on the different capacities of the battery cells 20, thereby obtaining a better thermal insulation effect. Specifically, the battery cell 20 is a ternary lithium battery, and the nickel element of the ternary positive electrode material in the battery cell 20 accounts for more than 0 and less than 50% of the atomic ratio of the ternary elements. Based on the different capacities of the battery cells 20, there are the following three solutions (1) to (3).

[0101] (1) The capacity of the battery cell 20 is less than 120Ah, the thickness of the composite phase change layer 13 is 1.5mm, and the thickness of the first insulation layer 11 and the second insulation layer 12 are independently 1mm to 1.5mm.

[0102] (2) The capacity of the battery cell 20 is ≥120 Ah and <215 Ah, the thickness of the composite phase change layer 13 is 2.3 mm, and the thickness of the first thermal insulation layer 11 and the second thermal insulation layer 12 are independently 1.5 mm to 2 mm.

[0103] (3) The capacity of the battery cell 20 is ≥215 Ah and <260 Ah, the thickness of the composite phase change layer 13 is 3.3 mm, and the thickness of the first heat insulation layer 11 and the second heat insulation layer 12 are independently 1.5 mm to 2 mm.

[0104] In this way, as the capacity of the battery cell 20 increases, the thickness of the composite phase change layer 13 increases accordingly, which can significantly improve the thermal insulation effect of the composite thermal insulation pad 10; in addition, compared with a simple thermal insulation layer, the thermal insulation effect of the composite thermal insulation pad 10 of the present application is greatly improved at the same total thickness, which is beneficial to reduce the volume occupied by the battery.

[0105] In some of the embodiments, the nickel element in the ternary positive electrode material in the battery cell 20 accounts for ≥50% and <70% of the atoms of the ternary elements, and the ternary positive electrode material is generally considered to be a medium-nickel ternary system; the thickness of the composite phase change layer 13 is 2.3mm~3.3mm, and the thickness of the first thermal insulation layer 11 and the second thermal insulation layer 12 are each independently 1.5mm~2.5mm.

[0106] Furthermore, in the case of the same battery cell 20 system, the present application optimizes the film thickness of the composite thermal insulation pad 10 based on the different capacities of the battery cells 20, thereby obtaining a better thermal insulation effect. Specifically, the battery cell 20 is a ternary lithium battery, and the nickel element of the ternary positive electrode material in the battery cell 20 accounts for ≥50% and <70% of the atomic ratio of the ternary elements. Based on the different capacities of the battery cells 20, there are the following three solutions (1) to (3).

[0107] (1) The capacity of the battery cell 20 is less than 150 Ah, the thickness of the composite phase change layer 13 is 2.3 mm to 3.3 mm, and the thickness of the first heat insulation layer 11 and the second heat insulation layer 12 are each independently 1.5 mm.

[0108] (2) The capacity of the battery cell 20 is ≥150 Ah and <200 Ah, the thickness of the composite phase change layer 13 is 2.3 mm to 3.3 mm, and the thickness of the first heat insulation layer 11 and the second heat insulation layer 12 are independently 1.5 mm to 2 mm.

[0109] (3) The capacity of the battery cell 20 is ≥200 Ah and <260 Ah, the thickness of the composite phase change layer 13 is 2.3 mm to 3.3 mm, and the thickness of the first thermal insulation layer 11 and the second thermal insulation layer 12 are each independently 1.5 mm to 2.5 mm.

[0110] Furthermore, in the case of the same battery cell 20 system, the present application optimizes the film thickness of the composite thermal insulation pad 10 based on the different capacities of the battery cells 20, thereby obtaining a better thermal insulation effect. The nickel element of the ternary positive electrode material in the battery cell 20 accounts for ≥70% of the atomic proportion of the ternary elements. Generally, the ternary positive electrode material is considered to be a high-nickel ternary system, and the proportion of nickel is <100%; the thickness of the composite phase change layer 13 is 1.5mm to 3.3mm, and the thickness of the first thermal insulation layer 11 and the second thermal insulation layer 12 are each independently 1mm to 2.5mm.

[0111] Furthermore, in the case of the same battery cell 20 system, the present application optimizes the film thickness of the composite thermal insulation pad based on the different capacities of the battery cells 20, thereby obtaining a better thermal insulation effect. Specifically, the battery cell 20 is a ternary lithium battery, and the nickel element of the ternary positive electrode material in the battery cell 20 accounts for ≥70% of the atomic proportion of the ternary elements. Based on the different capacities of the battery cells 20, there are the following three solutions (1) to (3).

[0112] (1) The capacity of the battery cell 20 is less than 100 Ah, the thickness of the composite phase change layer 13 is 1.5 mm, and the thickness of the first thermal insulation layer 11 and the second thermal insulation layer 12 are independently 1 mm to 1.5 mm;

[0113] (2) The capacity of the battery cell 20 is ≥100Ah and <120Ah, the thickness of the composite phase change layer 13 is 2.3 mm to 3.3 mm, and the thickness of the first thermal insulation layer 11 and the second thermal insulation layer 12 are independently 1 mm to 1.5 mm;

[0114] (3) The capacity of the battery cell 20 is ≥120 Ah, the thickness of the composite phase change layer 13 is 2.3 mm to 3.3 mm, and the thickness of the first thermal insulation layer 11 and the second thermal insulation layer 12 are each independently 2 mm to 2.5 mm.

[0115] In (1) and (2), as the capacity of the battery cell 20 increases, the thermal insulation effect of the composite thermal insulation pad 10 can be significantly improved by increasing the thickness of the composite phase change layer 13; in addition, compared with a simple thermal insulation layer, the thermal insulation effect of the composite thermal insulation pad 10 of the present application is greatly improved at the same total thickness, which is beneficial to reduce the volume occupied by the battery. In (2) and (3), as the capacity of the battery cell 20 continues to increase, the cost of continuing to increase the thickness of the composite phase change layer 13 is too high and the effect is not obvious. At this time, the thickness of the first thermal insulation layer 11 and the second thermal insulation layer 12 can be further increased, thereby improving the thermal insulation effect of the composite thermal insulation pad 10.

[0116] In some of the embodiments, the battery cell 20 is a lithium iron phosphate battery, the thickness of the composite phase change layer 13 is 1.5 mm to 3.3 mm, and the thickness of the first thermal insulation layer 11 and the second thermal insulation layer 12 are each independently 1 mm to 2 mm.

[0117] Furthermore, when the battery cell 20 system is the same, the present application optimizes the film thickness of the composite thermal insulation pad 10 based on the different capacities of the battery cells 20, thereby obtaining a better thermal insulation effect. Specifically, the battery cell 20 is a lithium iron phosphate battery, and based on the different capacities of the battery cells 20, there are the following three solutions (1) to (3).

[0118] (1) The capacity of the battery cell 20 is less than 160 Ah, the thickness of the composite phase change layer 13 is 1.5 mm, and the thickness of the first thermal insulation layer 11 and the second thermal insulation layer 12 are independently 1 mm to 1.5 mm;

[0119] (2) The capacity of the battery cell 20 is ≥160Ah and <260Ah, the thickness of the composite phase change layer 13 is 1.5 mm to 2.3 mm, and the thickness of the first thermal insulation layer 11 and the second thermal insulation layer 12 are each independently 1 mm to 1.5 mm;

[0120] (3) The capacity of the battery cell 20 is ≥260 Ah and <450 Ah, the thickness of the composite phase change layer 13 is 2.3 mm to 3.3 mm, and the thickness of the first thermal insulation layer 11 and the second thermal insulation layer 12 are each independently 1.5 mm to 2 mm.

[0121] In (1) and (2), as the capacity of the battery cell 20 increases, the thermal insulation effect of the composite thermal insulation pad 10 can be significantly improved by increasing the thickness of the composite phase change layer 13; in addition, compared with a simple thermal insulation layer, the thermal insulation effect of the composite thermal insulation pad 10 of the present application is greatly improved at the same total thickness, which is beneficial to reduce the volume occupied by the battery. In (2) and (3), as the capacity of the battery cell 20 continues to increase, the thickness of the composite phase change layer 13, the first thermal insulation layer 11 and the second thermal insulation layer 12 can be further increased, thereby improving the thermal insulation effect of the composite thermal insulation pad 10.

[0122] In some of the embodiments, the battery cell 20 is a sodium ion battery, the thickness of the composite phase change layer 13 is 1.5 mm to 2.3 mm, and the thickness of the first thermal insulation layer 11 and the second thermal insulation layer 12 are each independently 1 mm to 2 mm.

[0123] The sodium ion battery contains a sodium ion active material. As a non-limiting example of the sodium ion active material, the sodium ion active material may include one or more of the following materials: one or more of a sodium transition metal oxide, a polyanionic compound, and a Prussian blue compound. However, the present application is not limited to these materials, and other conventionally known materials that can be used as positive electrode active materials for sodium ion batteries may also be used.

[0124] Furthermore, when the battery cell 20 system is the same, the present application optimizes the film thickness of the composite thermal insulation pad 10 based on the different capacities of the battery cells 20, thereby obtaining a better thermal insulation effect. Specifically, the battery cell 20 is a sodium ion battery, and based on the different capacities of the battery cells 20, there are the following three solutions (1) to (3).

[0125] (1) The capacity of the battery cell 20 is less than 93 Ah, the thickness of the composite phase change layer 13 is 1.5 mm, and the thickness of the first heat insulation layer 11 and the second heat insulation layer 12 are independently 1 mm to 1.5 mm.

[0126] (2) The capacity of the battery cell 20 is ≥93 Ah and <117 Ah, the thickness of the composite phase change layer 13 is 1.5 mm to 2.3 mm, and the thickness of the first thermal insulation layer 11 and the second thermal insulation layer 12 are each independently 1 mm to 1.5 mm.

[0127] (3) The capacity of the battery cell 20 is ≥117 Ah and <180 Ah, the thickness of the composite phase change layer 13 is 1.5 mm, and the thickness of the first thermal insulation layer 11 and the second thermal insulation layer 12 are independently 1.5 mm to 2 mm.

[0128] In (1) and (2), as the capacity of the battery cell 20 increases, the thermal insulation effect of the composite thermal insulation pad 10 can be significantly improved by increasing the thickness of the composite phase change layer 13; in addition, compared with a simple thermal insulation layer, the thermal insulation effect of the composite thermal insulation pad 10 of the present application is greatly improved at the same total thickness, which is beneficial to reduce the volume occupied by the battery. In (2) and (3), as the capacity of the battery cell 20 continues to increase, the thickness of the first thermal insulation layer 11 and the second thermal insulation layer 12 can be further increased, thereby improving the thermal insulation effect of the composite thermal insulation pad 10.

[0129] Traditional technology is limited by structure, and phase change materials can only use solid phase change materials, but the heat absorption capacity of solid phase change materials is limited. The above-mentioned composite thermal insulation pad 10, because its phase change material layer 131 is arranged in the packaging cavity of the packaging layer 132, so that the phase change material layer 131 is physically isolated from the outer insulation layer, so the phase change material of its phase change material layer 131 can be a solid phase change material, a liquid phase change material or a solid-liquid mixed phase change material. Optionally, the phase change material includes but is not limited to crystal water and salt, phase change molten salt, paraffin, silicone oil, silica-alumina sol, fatty acids, alcohols and other substances that can undergo phase change and absorb heat, and its application range is wider.

[0130] In addition, because the phase change material of the phase change material layer 131 will undergo phase change, for example, the solid phase change material at room temperature will turn into liquid after absorbing heat, so the encapsulation layer 132 can also play the role of isolating the phase change material in liquid state after phase change from the outer heat insulation layer. In addition, some preparation processes inevitably make the phase change material contain moisture. The structure in which the phase change material layer 131 is arranged in the encapsulation cavity of the encapsulation layer 132 can prevent moisture overflow from causing adverse effects on the battery.

[0131] See also Figure 4 In some embodiments, the composite thermal insulation pad 10 further includes a first adhesive layer 151 and a second adhesive layer 152. The first thermal insulation layer 11 is connected to the encapsulation layer 132 via the first adhesive layer 151; the second thermal insulation layer 12 is connected to the encapsulation layer 132 via the second adhesive layer 152. In this way, the first thermal insulation layer 11, the composite phase change layer 13, and the second thermal insulation layer 12 of the composite thermal insulation pad 10 are connected and fixed in the thickness direction via the adhesive layer.

[0132] Furthermore, the material of the first adhesive layer 151 and the second adhesive layer 152 are each independently a silicone adhesive layer, and the thickness is independently 0.04 to 0.06 mm. The silicone adhesive layer is resistant to high temperatures and has high structural strength. The peeling force of the prepared composite thermal insulation pad is greater than 10N / cm. The peeling force can be measured by pulling the two sides of the composite thermal insulation pad with a tensile gauge, and applying a force perpendicular to the composite thermal insulation pad at 90° to the two sides of the composite thermal insulation pad. The tensile gauge will display the magnitude of the pulling force when the composite thermal insulation pad is peeled off, and the peeling force is obtained based on the magnitude of the pulling force.

[0133] In some embodiments, the composite thermal insulation pad 10 further includes a release adhesive layer (not shown). The release adhesive layer includes a third adhesive layer and a release film, wherein the third adhesive layer is disposed on the outer surface of the first thermal insulation layer 11 and the second thermal insulation layer 12, and the release film is disposed on the outer surface of the third adhesive layer. In this way, when the composite thermal insulation pad 10 needs to be fixed at a target position, such as a target battery cell, the release film on the surface of the release adhesive layer on the composite thermal insulation pad 10 is removed, and the composite thermal insulation pad 10 is simply and conveniently fixed to the target position by bonding with the third adhesive layer, thereby fixing the composite thermal insulation pad 10.

[0134] As an example, the above-mentioned release adhesive layer is provided on the outer surfaces of the first insulation layer 11 and the second insulation layer 12 of the composite insulation pad 10. When in use, the composite insulation pad 10 can be bonded and fixed to two objects respectively through the release adhesive layers on both sides, for example, bonded and fixed to two adjacent battery cells respectively, so that the composite insulation pad 10 is arranged between the two adjacent battery cells.

[0135] like Figure 4 As shown, the first thermal insulation layer 11 and the second thermal insulation layer 12 are physically separated by the composite phase change layer 13. In other words, the edges between the first thermal insulation layer 11 and the second thermal insulation layer 12 are not connected to each other.

[0136] In some embodiments, the length and width of the first thermal insulation layer 11 and the second thermal insulation layer 12 are respectively adapted to the length and width of the composite phase change layer 13. In other embodiments, at least one of the length and width of the first thermal insulation layer 11 and the second thermal insulation layer 12 is greater than the corresponding length or width of the composite phase change layer 13.

[0137] See also Figure 5 In some embodiments, the edges of the first thermal insulation layer 11 and the second thermal insulation layer 12 are connected to each other to form an assembly cavity, and the composite phase change layer 13 is located in the assembly cavity. With this structural setting, the composite phase change layer 13 is arranged inside the first thermal insulation layer 11 and the second thermal insulation layer 12, reducing the risk of the composite phase change layer 13 falling off.

[0138] Further, at least one side surface edge of at least one of the first thermal insulation layer 11 and the second thermal insulation layer 12 forms a convex portion, and the convex portion encloses at least part of the assembly cavity. As an example, at least one side surface edge of the first thermal insulation layer 11 and the second thermal insulation layer 12 forms a convex portion, and the convex portions of the two are arranged opposite to each other and enclose to form an assembly cavity. Figure 5 In the specific example, convex portions are formed around the edges of one side surface of the first thermal insulation layer 11 and the second thermal insulation layer 12, and the convex portions of the first thermal insulation layer 11 and the second thermal insulation layer 12 are arranged opposite to each other and enclose to form an assembly cavity.

[0139] Generally, the two sides of the phase change material layer 131 are encapsulated by an encapsulation film, and there are encapsulation margins on the sides, such as the following Fig. 9 That is, the encapsulation layer 132 has an encapsulation margin. When the composite phase change layer 13 is disposed inside the first heat insulation layer 11 and the second heat insulation layer 12, the encapsulation margin is folded and located in the assembly cavity.

[0140] As an example, the encapsulation layer 132 has an encapsulation margin on all four sides.

[0141] See also Figure 6In some embodiments, the composite thermal insulation pad 10 further includes a third thermal insulation layer 16, and a composite phase change layer 13 is also provided between the second thermal insulation layer 12 and the third thermal insulation layer 16. Furthermore, the composite thermal insulation pad 10 may further include more thermal insulation layers, and the composite phase change layer 13 may also be provided between the second thermal insulation layer 12 and the third thermal insulation layer 16.

[0142] Furthermore, the selection range of the material and thickness of the third thermal insulation layer 16 and other thermal insulation layers can be the same as that of the first thermal insulation layer 11 and the second thermal insulation layer 12; the specific material and specific thickness can be the same or different.

[0143] See also Figure 7 and Figure 8 In some embodiments, the composite thermal insulation pad 10 also includes a first packaging frame 141 and a second packaging frame 142. The first packaging frame 141 is arranged on one side of the first thermal insulation layer 11, and the second packaging frame 142 is arranged on one side of the second thermal insulation layer 12. The first packaging frame 141 and the second packaging frame 142 cooperate to fix the first thermal insulation layer 11, the composite phase change layer 13 and the second thermal insulation layer 12.

[0144] Further, the first packaging frame 141 and the second packaging frame 142 are each independently a rubber frame or a silicone frame. In other words, the materials of the first packaging frame 141 and the second packaging frame 142 are each independently rubber or silicone. Further, the first packaging frame 141 and the second packaging frame 142 are both shaped frames, such as silicone shaped frames.

[0145] In such Figure 8 and Fig. 9 In the example shown, the first packaging frame 141 has a first limiting groove (not shown), the second packaging frame 142 has a second limiting groove (not shown), and the first thermal insulation layer 11, the composite phase change layer 13 and the second thermal insulation layer 12 are limited in the limiting space formed by the first limiting groove and the second limiting groove. The first limiting groove and the second limiting groove can limit the first thermal insulation layer 11, the composite phase change layer 13 and the second thermal insulation layer 12 in the thickness direction and the radial direction of the composite thermal insulation pad 10, thereby improving the structural stability of the composite thermal insulation pad 10. Among them, the radial direction of the composite thermal insulation pad 10 refers to the direction from the center of the composite thermal insulation pad 10 to the edge of the composite thermal insulation pad 10. Furthermore, at this time, the packaging margin portion 1321 of the packaging layer 132 can be located between the first packaging frame 141 and the second packaging frame 142, such as Fig. 9 As shown, the package margin portion 1321 is pressed in the middle by the first package frame 141 and the second package frame 142 .

[0146] It can be understood that when the above-mentioned first packaging frame 141 and second packaging frame 142 and the above-mentioned first thermal insulation layer 11 and second thermal insulation layer 12 capable of forming an assembly cavity are provided at the same time, the packaging margin portion 1321 of the packaging layer 132 can pass through between the convex portions of the first thermal insulation layer 11 and the second thermal insulation layer 12 and be located between the first packaging frame 141 and the second packaging frame 142, or the packaging margin portion 1321 of the packaging layer 132 can also be folded and located in the assembly cavity.

[0147] See also Fig.10 In other embodiments, the outer surface of the first thermal insulation layer 11 is flush with the outer surface of the first packaging frame 141, and / or the outer surface of the second thermal insulation layer 12 is flush with the outer surface of the second packaging frame 142. In this way, the thickness of the composite thermal insulation pad 10 can be minimized, the space it occupies can be reduced, and better thermal insulation performance can be provided.

[0148] As an example, on the basis of the first adhesive layer 151 and the second adhesive layer 152, the first packaging frame 141 and the second packaging frame 142 can be further used to fix the first thermal insulation layer 11, the composite phase change layer 13 and the second thermal insulation layer 12 around, thereby improving the structural stability of the composite thermal insulation pad 10. Furthermore, at this time, there is no need for the packaging frame to fix the thickness direction, so the outer surface of the first thermal insulation layer 11 can be flush with the outer surface of the first packaging frame 141, and the outer surface of the second thermal insulation layer 12 can be flush with the outer surface of the second packaging frame 142.

[0149] It can be understood that in some embodiments, the first thermal insulation layer 11, the composite phase change layer 13, the second thermal insulation layer 12, and the third thermal insulation layer 16 can be connected by the above-mentioned adhesive layer, or by the above-mentioned packaging frame, or by both the above-mentioned adhesive layer and the packaging frame, or by none of them, for example, the first thermal insulation layer 11 is directly formed on the packaging layer 132 of the composite phase change layer 13.

[0150] Furthermore, the first thermal insulation layer 11, the second thermal insulation layer 12 and the third thermal insulation layer 16 each independently include at least one of thermal insulation felt and thermal insulation coating.

[0151] Furthermore, when any of the above-mentioned thermal insulation layers includes both of the thermal insulation felt and the thermal insulation coating, the thermal insulation coating may be optionally disposed on a side closer to the composite phase change layer 13, specifically, the thermal insulation coating is disposed on the surface of the encapsulation layer 132 of the composite phase change layer 13, and the thermal insulation felt is disposed on a side further away from the composite phase change layer 13. In other words, the thermal insulation coating is directly formed on the surface of the encapsulation layer 132, and the thermal insulation coating is located between the encapsulation layer 132 and the thermal insulation felt.

[0152] For example, Figure 3 , Figure 4 and Figure 6In the example, the first thermal insulation layer 11 and the second thermal insulation layer 12 are thermal insulation felts, and the third thermal insulation layer 16 is also thermal insulation felt. In other examples, the first thermal insulation layer 11 and the second thermal insulation layer 12 may also be thermal insulation coatings. In comparison, the thickness of the thermal insulation coating is thinner, the overall thickness of the prepared composite thermal insulation pad is thinner, and the required space is relatively smaller. The thermal insulation layer of the composite thermal insulation pad 10 can optionally adopt a thermal insulation coating, or a composite of a thermal insulation coating and ceramic felt, which can take into account both smaller occupied space and better thermal insulation performance.

[0153] For example, in Figure 5 In the example shown, the first thermal insulation layer 11 and the second thermal insulation layer 12 are thermal insulation felts, and the assembly cavity thereon can be integrally formed when the thermal insulation felt is formed, or can be formed by grooving after the thermal insulation felt is formed.

[0154] It is understood that the thermal insulation felt can be connected to the composite phase change layer 13 through the above-mentioned adhesive layer or packaging frame. The thermal insulation coating can be directly formed on the packaging layer 132 in the composite phase change layer 13. As an example, the thermal insulation coating can be prepared by coating the packaging layer 132 of the composite phase change layer 13 with a slurry and then drying it to form a coating.

[0155] Furthermore, the thermal insulation felt may be a ceramic thermal insulation felt; further, the thermal insulation coating may be a ceramic thermal insulation coating.

[0156] In some of the embodiments, the first thermal insulation layer 11, the second thermal insulation layer 12 and the third thermal insulation layer 16 each independently meet the following conditions: the thermal conductivity at 25°C is ≤0.020W / m·K, the thermal conductivity at 200°C is ≤0.027W / m·K, the thermal conductivity at 300°C is ≤0.035W / m·K, and the thermal conductivity at 500°C is ≤0.080W / m·K.

[0157] In some embodiments, the density of the first thermal insulation layer 11, the second thermal insulation layer 12, and the third thermal insulation layer 16 is independently 0.2 to 0.22 g / cm 3 .

[0158] In this article, the following method can be used to test the thickness of the composite thermal insulation pad. The equipment used is the Mitutoyo 547-301 thickness gauge, and the accuracy of the equipment is ≤0.01mm; during the test, the test surface of the composite thermal insulation pad and the Mitutoyo 547-301 thickness gauge are required to be parallel to the ground, and the test positions are 5 points in the four corners and the center area, and the average value of the 5 points is taken as the test value.

[0159] In some embodiments, the first heat insulating layer 11 is a ceramic material layer.

[0160] In some embodiments, the second thermal insulation layer 12 is a ceramic material layer.

[0161] The material in the "ceramic material layer" in the present application includes but is not limited to at least one of ceramic oxides, ceramic nitrides, and ceramic carbides. Among them, ceramic oxides include but are not limited to at least one of silicon oxide and aluminum oxide, ceramic nitrides include but are not limited to silicon nitride, and ceramic carbides include but are not limited to silicon carbide.

[0162] In some examples, the ceramic material layer may be a stack of one or more of a silicon oxide layer, an aluminum oxide layer, a silicon nitride layer, and a silicon carbide layer.

[0163] Furthermore, the ceramic insulation felt may be a silica aerogel ceramic felt. As an example, the silica aerogel ceramic felt may be prepared by inorganic fiber reinforcement technology to prepare aerogel materials, through impregnation sol, gel, solvent replacement and supercritical drying processes.

[0164] In some of the embodiments, the thickness of the packaging layer 132 is 0.1 mm to 0.3 mm, for example, 0.1 mm, 0.15 mm, 0.2 mm, 0.3 mm, and can be optionally 0.1 mm to 0.15 mm, or 0.2 mm to 0.3 mm.

[0165] In some embodiments, the packaging layer 132 is an aluminum-plastic film or a polymer packaging film.

[0166] Further, the packaging layer 132 includes a polypropylene layer, an aluminum layer, and a nylon layer stacked from inside to outside.

[0167] Furthermore, the polymer packaging film may be a PET film (polyethylene terephthalate film) or a PI film (polyimide film).

[0168] In some embodiments, a weak portion is provided on the area of ​​the packaging layer 132 constituting the packaging cavity. Since the weak portion is located at a weak area, when the phase change material layer 131 absorbs more heat, the phase change material in the phase change material layer 131 undergoes a phase change, causing the packaging layer 132 to bulge, so that the packaging layer 132 can be broken in time from the weak portion when thermal runaway occurs, further reducing the degree of damage to the battery as a whole caused by thermal runaway.

[0169] It can be understood that the weak portion on the encapsulation layer 132 is a region on the encapsulation layer 132 where the strength is relatively weak.

[0170] In some embodiments, the weak portion is a region with a thinner thickness and / or a weaker material strength. In other words, the weak portion can be a region with a thinner thickness but a constant material strength, which can be formed by locally thinning the encapsulation layer 132. The weak portion can also be a region with a constant thickness but a weaker material strength, which can be formed by locally weakening the material strength of the encapsulation layer 132, for example, by using materials of different strengths. It can also be a region with a thinner thickness and a weaker material strength. It is understandable that the material strength here refers to the strength of the material itself.

[0171] Further, the weak portion is a notch area formed on the encapsulation layer 132. It can be understood that the notch area is formed by thinning the surface of the encapsulation layer 132 in the form of engraving and pressing, and the thickness of the notch area is relatively thin.

[0172] Furthermore, the weak portion may be disposed on the outer side or the inner side of the encapsulation layer 132. The outer side refers to the surface of the encapsulation layer 132 away from the phase change material layer 131, and the inner side refers to the surface of the encapsulation layer 132 close to the phase change material layer 131.

[0173] Furthermore, the depth of the weak portion accounts for 15% to 50% of the thickness of the packaging layer 132, for example, 15%, 20%, 30%, 35%, 40%, 45%, 50%. By controlling the thickness ratio, the packaging layer can take into account both a better isolation effect when no package breakage is required and a better timely package breakage effect in the event of thermal runaway.

[0174] Furthermore, the aluminum-plastic film comprises an aluminum foil layer and plastic film layers arranged on two surfaces of the aluminum foil layer.

[0175] Furthermore, when the encapsulation layer 132 is an aluminum-plastic film, the weak portion penetrates from the surface of the aluminum-plastic film to 30% to 60% of the thickness of the aluminum foil layer, for example, 30%, 40%, 50%, or 60%. The weak portion is controlled to penetrate into the aluminum foil layer, but does not penetrate the aluminum foil layer, and is further controlled to penetrate to 30% to 60% of the thickness of the aluminum foil layer, so that the encapsulation layer can take into account both better isolation when no package breaking is required and better timely package breaking in case of thermal runaway.

[0176] The plastic film layer in the aluminum-plastic film may include but is not limited to at least one of a polypropylene layer, a nylon layer and a polyester layer. In some examples, the encapsulation layer 132 includes a polypropylene layer, an aluminum foil layer, a nylon layer and a polyester layer stacked from the inside to the outside. As a specific example, the thickness of the polypropylene layer, the aluminum foil layer, the nylon layer and the polyester layer are 80 μm, 40 μm, 15 μm and 6 μm respectively, and the weak portion can be deep from one side of the polyester layer to the position of half the thickness of the aluminum foil layer.

[0177] In some embodiments, the phase change material layer 131 includes a heat insulation substrate in addition to the phase change material, and at least part of the phase change material is filled in the pores of the heat insulation substrate. In other words, the pores of the heat insulation substrate are filled with the phase change material.

[0178] The thermal insulation substrate may be a ceramic material substrate, such as ceramic fiber felt.

[0179] Furthermore, in some examples, at least part of the phase change material is directly filled in the pores of the thermal insulation substrate. In other examples, the phase change material can also be filled in the pores of the thermal insulation substrate in the form of phase change microcapsules. It is understood that in the same thermal insulation substrate, two states of phase change materials can also be included at the same time, one is that the phase change material is directly filled in the pores of the thermal insulation substrate, and the other is that the phase change material is filled in the pores of the thermal insulation substrate in the form of phase change microcapsules.

[0180] It can be understood that the phase change material layer 131 can be obtained by soaking the porous thermal insulation substrate such as ceramic fiber felt in the liquid phase change material, for example, soaking in the molten phase change material and then cooling it or soaking in the phase change material solution and then drying or heat preservation. In addition to absorbing heat, the phase change material layer 131 can also play a role in heat insulation. When the phase change material vaporizes and breaks the packaging layer 132, that is, the composite thermal insulation pad 10 fails, the thermal insulation substrate in the phase change material layer 131 can continue to play a role in heat insulation. In other words, the phase change material is directly filled in the pores of the thermal insulation substrate.

[0181] In other embodiments, at least part of the phase change material is filled in the pores of the thermal insulation substrate in the form of phase change microcapsules. In other words, the pores of the thermal insulation substrate of the phase change material layer 131 can be filled with phase change microcapsules. The phase change microcapsules include a core material and a wall material, the wall material is wrapped around the outer surface of the core material, and the core material includes a phase change material. It can be understood that in some examples, the pores of the thermal insulation substrate can also be directly filled with phase change materials and the above-mentioned phase change microcapsules at the same time.

[0182] The above-mentioned phase change material layer 131 can be obtained by dispersing phase change microcapsules in a solvent to obtain a phase change microcapsule dispersion, then immersing a thermal insulation substrate in the phase change microcapsule dispersion to fill the phase change microcapsules in the pores of the thermal insulation substrate, and removing the solvent in the phase change microcapsule dispersion.

[0183] In this way, the phase change microcapsules in the phase change material layer 131 absorb heat. When the battery cell thermally runs away, the phase change material in the adjacent composite insulation pad 10 vaporizes and breaks the packaging layer 132, that is, the composite insulation pad 10 fails. At this time, the insulation substrate in the phase change material layer 131 can continue to play an insulation role.

[0184] Further, the wall material includes a polymer matrix and ceramic particles filled in the polymer matrix. Further, the mass ratio of the polymer matrix to the ceramic particles is 3:(7-11), and as an example, the mass ratio of the polymer matrix to the ceramic particles can be 3:7, 3:8, 3:9, 3:10, 3:11. By controlling the mass content of the ceramic particles in the wall material to be larger, the pressure resistance and heat insulation capacity of the wall material can be improved.

[0185] Furthermore, the mass ratio of the polymer matrix to the core material is 1:(1.3-1.6), and as an example, the mass ratio of the polymer matrix to the core material can be 1:1.3, 1:1.4, 1:1.5, 1:1.6. This can further improve the pressure resistance of the phase change microcapsules.

[0186] Furthermore, the polymer matrix includes but is not limited to any one of phenolic resin, polyacrylonitrile resin, melamine formaldehyde resin, etc. The polymer matrix not only has good insulation, but also has good compatibility with phase change materials such as paraffin wax, can form a stable interface with the phase change material, and improve the thermal stability of the phase change microcapsules.

[0187] Furthermore, the Dv50 particle size of the phase change microcapsule is 5 to 8 μm. The Dv50 particle size is the volume average particle size Dv50, which indicates the particle size corresponding to when the cumulative volume distribution percentage of the particles reaches 50%, and can be tested by methods known in the art. For example, it can be measured using a laser particle size analyzer (such as Malvern Master Size 3000).

[0188] Furthermore, the thermal conductivity of the wall material at 25° C. is ≥ 0.32 W / mK. Such a wall material has a good thermal conductivity and can better conduct heat to the phase change material inside it.

[0189] Furthermore, the melting point of the wall material is greater than 98° C. The wall material has a relatively high melting point, and can maintain the structural stability of the microcapsule within the phase change temperature range of the phase change material.

[0190] The material selection of the above-mentioned thermal insulation substrate and ceramic particles in this application is the same as the selection range of the above-mentioned ceramic material layer. In some examples, the above-mentioned thermal insulation substrate is a ceramic fiber mat. The ceramic fiber mat has ceramic fiber as the core skeleton, which can not only well infiltrate the liquid phase change material so that the phase change material is filled in the pores of its core skeleton, but also has low thermal conductivity, good high temperature resistance (1280°C), resistance to instantaneous thermal shock, flame retardant properties and mechanical properties, no powdering, and is flexible and resilient, which is compatible with the battery pack manufacturing process.

[0191] In some examples, the ceramic particles include but are not limited to at least one of boron nitride particles, silicon nitride particles, silicon carbide particles, silicon dioxide particles, etc. Further, the Dv50 of the ceramic particles is 60 to 90 nm. As an example, the Dv50 of the ceramic particles can be any value of 60 nm, 65 nm, 70 nm, 75 nm, 80 nm, 83 nm, 85 nm, 90 nm or between any two values. The silicon dioxide particles of the above specific particle size are conducive to doping and uniform dispersion in the substrate.

[0192] Phase-change microcapsules can be obtained by in-situ polymerization, where the wall material covers the core material. In some examples, the preparation method of phase-change microcapsules includes the following steps: dispersing ceramic particles in water to form an aqueous phase; heating the phase-change material to a molten state to form an oil phase; mixing the aqueous phase and the oil phase, stirring to form a Pickering emulsion, adding the raw materials required for preparing the polymer matrix of the wall material (such as water-soluble polymer monomers or prepolymer aqueous solutions) to the Pickering emulsion, and stirring and polymerizing at room temperature to generate a non-water-soluble polycondensate (i.e., a polymer matrix) with a cross-linked three-dimensional network structure at the interface of the emulsion.

[0193] The polymer matrix of the above material has better compatibility with phase change materials such as paraffin, and also facilitates the uniform dispersion of ceramic particles, thereby ensuring the stability of phase change microcapsules.

[0194] Furthermore, the battery 30 includes a plurality of battery cells 20, and the composite thermal insulation pad 10 is disposed between at least two adjacent battery cells 20. Generally, a battery includes a plurality of battery cells, and the systems and capacities of the plurality of battery cells are the same.

[0195] Optionally, a composite heat-insulating pad 10 is provided between any two adjacent battery cells 20. It is understandable that the composite heat-insulating pad 10 may also be provided between the battery cells 20 and the inner wall of the housing of the battery 30.

[0196] It is understood that the shape of the battery cell 20 includes but is not limited to a square or a cylinder. The composite thermal insulation pad 10 can be arranged in a manner that is consistent with the shape of the battery cell 20 .

[0197] In some of the embodiments, the battery cell 20 is square, and the composite thermal insulation pad 10 is disposed on the side surface of the battery cell 20 with a larger area (ie, the large surface) to increase its contact area and improve the thermal insulation performance.

[0198] It is understandable that after a plurality of battery cells 20 are connected to each other and arranged in a certain order, they can be directly placed in a box to assemble into a battery. Alternatively, a plurality of battery cells 20 can be first formed into a battery module, and then a plurality of battery modules are connected to each other to form a whole, and finally the whole battery module is placed in a box to form a battery.

[0199] Fig.11 The battery cell 20 is a square structure as an example. The battery cell 20 includes a housing 21, a cover plate 23 and an electrode assembly 22. The housing 21 has an opening, the electrode assembly 22 is accommodated in the housing 21, and the cover plate 23 is sealed at the opening. The electrode assembly 22 includes a positive electrode sheet, a negative electrode sheet and a separator. The positive electrode sheet, the negative electrode sheet and the separator can be formed by a winding process or a lamination process.

[0200] Furthermore, the electrode assembly 22 also includes an electrolyte, such as an electrolyte. The electrolyte is infiltrated in the electrode assembly 22. The number of electrode assemblies 22 included in the battery cell 20 can be one or more, and those skilled in the art can select according to specific actual needs.

[0201] Furthermore, one or both ends of the housing 21 are provided with an opening.

[0202] Further, the housing 21 is a rectangular housing, and the opening direction of the housing 21 is the height direction of the housing 21. Further, both ends of the housing 21 are provided with openings, and the two openings are arranged oppositely along the height direction of the housing 21. Further as a non-limiting example, the height of the housing 21 is 80 mm to 210 mm; further as a non-limiting example, the length of the housing 21 is 90 mm to 240 mm; further as a non-limiting example, the width of the housing 21 is 20 mm to 80 mm.

[0203] Furthermore, the battery cell 20 and the shell 21 are rectangular shells, and the composite insulation pad 10 is arranged on the larger side of the battery cell 20, which is perpendicular to the above-mentioned width direction, that is, the side formed by the two sides of the above-mentioned length direction and height direction.

[0204] As a further non-limiting example, the wall thickness of the housing is 0.5 mm to 0.8 mm.

[0205] Furthermore, the shell is an aluminum alloy shell; for example, a three-series aluminum alloy shell or a five-series aluminum alloy shell.

[0206] Furthermore, the aluminum alloy of the three-series aluminum alloy shell includes the following components in mass percentage: aluminum ≥ 99.6%, copper ≤ 0.05%, iron ≤ 0.35%, magnesium ≤ 0.03%, manganese ≤ 0.03%, silicon ≤ 0.25%, titanium ≤ 0.03%, vanadium ≤ 0.05%, zinc ≤ 0.05%, and other single elements ≤ 0.03%.

[0207] Furthermore, the aluminum alloy of the fifth series aluminum alloy shell includes the following components in percentage by mass: aluminum ≥ 96.7%, 0.05% ≤ copper ≤ 0.2%, iron ≤ 0.7%, manganese ≤ 1.5%, silicon ≤ 0.6%, zinc ≤ 0.1%, other single element components ≤ 0.05%, and the total components of other elements ≤ 0.15%.

[0208] Furthermore, the electrode assembly 22 also includes an electrolyte. The electrolyte is infiltrated in the electrode assembly 22. The number of electrode assemblies 22 included in the battery cell 20 can be one or more, and those skilled in the art can select according to specific actual needs.

[0209] The working principle of the battery using the above-mentioned composite thermal insulation pad 10 is as follows: In the first stage, after a battery cell 20 in the battery 30 has thermal runaway, the heat is transferred to the adjacent (for example, adjacent) composite thermal insulation pad 10, and the phase change material layer 131 in the composite thermal insulation pad 10 absorbs heat to prevent the thermal runaway of the battery. In the second stage, the phase change material layer 131 absorbs heat until a phase change occurs, absorbing a large amount of heat. In the third stage, the encapsulation layer 132 and the phase change material layer 131 fail: the phase change material in the phase change material layer 131 is converted into a gaseous state and breaks through the encapsulation layer 132, discharging the high-temperature gas. In the fourth stage, the first thermal insulation layer 11 and the second thermal insulation layer 12 and the optional thermal insulation substrate in the composite phase change layer 13 continue to play a role in thermal insulation.

[0210] Among them, the first stage and the second stage are the states before the composite thermal insulation pad 10 fails, and the third stage and the fourth stage are the states after the composite thermal insulation pad 10 fails.

[0211] Another embodiment of the present application further provides an electrical device, including the above-mentioned battery provided in the present application. The above-mentioned battery can be used as a power source for the electrical device, and can also be used as an energy storage unit for the electrical device. The electrical device may include mobile devices, electric vehicles, electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto. Among them, the mobile device may be, for example, a mobile phone, a laptop computer, etc.; the electric vehicle may be, for example, a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc., but are not limited thereto.

[0212] As an electrical device, a secondary battery, a battery module or a battery pack can be selected according to its usage requirements.

[0213] Fig.12 The power consumption device 40 is taken as an example. The power consumption device 40 is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. In order to meet the power consumption device's requirements for high power and high energy density of secondary batteries, a battery pack or a battery module may be used.

[0214] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a secondary battery may be used as a power source.

[0215] The following are specific embodiments.

[0216] Specifically, the following is a battery of Example 1. The battery includes two battery cells (i.e., battery cores) and a composite thermal insulation pad disposed between the two battery cells; the two battery cells are both five-series battery cells, i.e., NCM 523The battery cells have a capacity of 215Ah. The composite thermal insulation pad includes a first thermal insulation layer, a composite phase change layer and a second thermal insulation layer which are stacked; the first thermal insulation layer and the second thermal insulation layer are both silica aerogel ceramic felt, the composite phase change layer includes a phase change material layer and a packaging layer arranged on the outer peripheral side of the phase change material layer, the packaging layer is an aluminum-plastic film with a thickness of 0.2mm, and the phase change material in the phase change material layer is CaCl2·6H2O.

[0217] The above-mentioned battery was tested as follows: By triggering the thermal runaway of the first battery cell (referred to as A battery cell), the thermal insulation performance of the composite thermal insulation pad on the second battery cell (referred to as B battery cell) was examined. At the same time, the overall thickness of the composite thermal insulation pad was kept unchanged, and the thickness of each layer of the first thermal insulation layer, the composite phase change layer and the second thermal insulation layer was adjusted to examine the influence of the internal film layer thickness of the composite thermal insulation pad on the thermal insulation performance of the composite thermal insulation pad. The specification of the composite thermal insulation pad is a rectangle of size 100mm×100mm, with a total thickness of 6.3mm. The thickness of each film layer is shown in Table 2.

[0218] The test method is as follows: Heat the heating table. Install temperature sensing wires on the two large surfaces of the A battery cell and the two large surfaces of the B battery cell respectively, place the above battery on the heating table, and press the above battery with an aluminum plate with a pressure of 3000N. By measuring the temperature of the two large surfaces of the A battery cell and the two large surfaces of the B battery cell within 1000s or 2000s, the thermal insulation effect of the thermal insulation pad can be determined. There are 3 temperature sampling points on each surface, one is the center point, and the other two are distributed symmetrically with the center point, and the spacing between them is 15mm.

[0219] The thermal diffusion time (measured value) of batteries 1 to 4 obtained through the above test is shown in Table 2, where battery 1 is a pure thermal insulation pad without a composite phase change layer, and "2mm+2.3mm+2mm" in battery 2 indicates that the thicknesses of the first thermal insulation layer, the composite phase change layer and the second thermal insulation layer of the composite thermal insulation pad are 2mm, 2.3mm and 2mm respectively, and the others are similar.

[0220] Table 2

[0221]

[0222]

[0223] The measured curves of thermal insulation performance of battery 2 and battery 3 are as follows: Fig.13 and Fig.14 As shown in curves 1a to 1d.

[0224] Among them, the large surface of the A cell refers to the large surface of the A cell that is in direct contact with the heating platform, and the other side opposite to it is the back of the A cell. The large surface of the B cell refers to the large surface of the B cell that is in direct contact with the composite insulation pad, and the other side opposite to it is the back of the B cell.

[0225] from Fig.13 It can be seen that within the test time of 2000s, within the first 1150s, when the hot surface temperature of the large surface of the A battery cell reaches nearly 900°C, due to the thermal insulation effect of the composite thermal insulation pad, the maximum temperature of the large surface of the B battery cell does not exceed 250°C, and the temperature on the back of the B battery cell does not exceed 100°C. Within the first 1150s, the temperature of the large surface of the B battery cell is basically maintained at a temperature platform near 250°C from the highest temperature of the large surface of the A battery cell. The duration corresponding to this temperature platform (the temperature platform between the highest temperature of the large surface of the A battery cell and the inflection point of the temperature rise of the large surface of the B battery cell) is the thermal diffusion time in Table 2.

[0226] from Fig.14 It can be seen that within the test time of 1000s, within the first 700s, when the hot surface temperature of the large surface of the A battery cell reaches nearly 900℃, due to the thermal insulation effect of the composite thermal insulation pad, the maximum temperature of the large surface of the B battery cell does not exceed 350℃, and the temperature on the back of the B battery cell does not exceed 100℃. Within the first 700s, the temperature of the large surface of the B battery cell is basically maintained at a temperature platform near 250℃ from the highest temperature of the large surface of the A battery cell. The duration corresponding to this temperature platform (the temperature platform between the highest temperature of the large surface of the A battery cell and the inflection point of the temperature rise of the large surface of the B battery cell) is the thermal diffusion time in Table 2.

[0227] It can be seen from Table 2 that when the thickness of the composite thermal insulation pad is the same, the thermal insulation performance of the composite thermal insulation pads of batteries 2 to 3 is better, and the thermal insulation performance of the composite thermal insulation pad of battery 2 is the best. For battery 2, which is a ternary lithium battery cell in which the atomic proportion of nickel in the ternary elements is ≥50% and <70%, the thickness of the composite phase change layer is 2.3mm~3.3mm, and the thickness of the first thermal insulation layer and the second thermal insulation layer are both 1.5mm~2.5mm. Furthermore, the capacity of the battery cell is 215Ah, which is within the range of battery cell capacity ≥150Ah and <200Ah. Optionally, the thickness of the composite phase change layer is 2.3mm~3.3mm, and the thickness of the first thermal insulation layer and the second thermal insulation layer are each independently 1.5mm~2mm.

[0228] In some embodiments, the film thickness of the composite thermal insulation pad can be obtained by simulation and screening of the heat estimation model. The thermal diffusion time (simulation value) of batteries 1 to 4 obtained by simulation of the heat estimation model is shown in Table 2. The simulation test curves of the thermal insulation performance of batteries 2 and 3 are shown in Table 2. Fig.13 and Fig.14 As shown in curves 2a to 1d. By comparing the measured values ​​with the simulation values, it can be seen that the error between the two is within 15%. As shown in Table 2, the thickness composition of the composite thermal insulation pad is screened by the measured values ​​and / or simulation values ​​of the thermal diffusion time. In the above Table 2 of this application, the thickness of the composite thermal insulation pad is verified by actual measurement and heat estimation model simulation for different battery cell systems and capacities.

[0229] like Fig.15 The method for testing a battery using a heat estimation model is shown. The test method can obtain test data, from which a heat diffusion time simulation value can be obtained. The following is an example of the method being applied to Fig.16 The computer device in FIG. 1 is used as an example to illustrate. The computer device may be a terminal, and its internal structure diagram may be as shown in FIG. Fig.16 As shown. The computer device includes a processor, a memory, a communication interface, a display screen and an input device connected via a system bus. Among them, the processor of the computer device is used to provide computing and control capabilities. The memory of the computer device includes a non-volatile storage medium and an internal memory. The non-volatile storage medium stores an operating system and a computer program. The internal memory provides an environment for the operation of the operating system and the computer program in the non-volatile storage medium. The communication interface of the computer device is used to communicate with an external terminal in a wired or wireless manner, and the wireless manner can be achieved through WIFI, a mobile cellular network, NFC (near field communication) or other technologies. When the computer program is executed by the processor, a battery testing method is implemented. The display screen of the computer device can be a liquid crystal display screen or an electronic ink display screen, and the input device of the computer device can be a touch layer covering the display screen, or a button, trackball or touchpad set on the computer device housing, or an external keyboard, touchpad or mouse, etc. Those skilled in the art can understand that Fig.16 The structure shown in the figure is only a block diagram of a part of the structure related to the solution of the present application, and does not constitute a limitation on the computer device to which the solution of the present application is applied. The specific computer device may include more or fewer components than those shown in the figure, or combine certain components, or have a different arrangement of components.

[0230] The method for testing the battery using the thermal estimation model includes the following steps:

[0231] S201, responding to an input instruction triggered by a user on a test interface, obtaining property parameters of a battery to be tested.

[0232] Among them, the input instruction is used to obtain the attribute parameters of the battery to be tested input by the user on the test interface, which carries the attribute parameters of the battery to be tested. The attribute parameters are related parameters for calculating the thermal diffusion performance of the battery. The test interface is the interface of the test application or simulation software, for example, when the test APP is used to test the battery, the test interface of the test APP. The test application or simulation software can realize the construction of a simulation model for the battery and test based on the simulation model.

[0233] In the embodiment of the present application, a test application (e.g., a battery simulation APP) or simulation software is pre-installed on the computer device, and the test application or simulation software can be operated to simulate the battery, thereby guiding the design of the battery. When it is necessary to test the thermal runaway battery or battery, the test application or simulation software for simulating the battery can be started on the computer device, and the test interface corresponding to the test application or simulation software can be displayed on the display screen of the computer device. The user can enter the attribute parameters of the battery to be tested on the test interface. After the user enters the attribute parameters, the computer device can generate an input instruction carrying the attribute parameters, and the computer device can immediately respond to the input instruction triggered by the user on the test interface, parse the input instruction, extract the attribute parameters of the battery to be tested, and obtain the attribute parameters of the battery to be tested. Optionally, after the user enters the attribute parameters of the battery on the test interface, the computer device can also store the attribute parameters in the cache, and when the computer device responds to the input instruction, the attribute parameters can be obtained from the cache according to the instruction of the input instruction.

[0234] S202, in response to a test instruction triggered by a user on a test interface, inputting attribute parameters into a heat estimation model for measurement, obtaining test data of the battery to be tested, and displaying the test data on the test interface.

[0235] Among them, the test instruction is used to start the test of the battery to be tested, that is, to test according to the attribute parameters and the heat estimation model, so as to test the simulated battery to be tested. The heat estimation model is used to measure the influence of the thermal diffusion of the battery according to the attribute parameters. The test data includes the temperature change data of the large surface of each thermal runaway cell in the battery to be tested and the temperature change data of the bottom surface of the cell. For example, the battery to be tested includes thermal runaway cell A and thermal runaway cell B, and the test data includes the temperature change data of the large surface of the cell of thermal runaway cell A over time, the temperature change data of the bottom surface of the cell of thermal runaway cell A over time, the temperature change data of the large surface of the cell of thermal runaway cell B over time, and the temperature change data of the bottom surface of the cell of thermal runaway cell B over time. The heat estimation model can be pre-built and stored in a database, which can include various types of battery test models to provide a calculation method for battery performance testing. Optionally, the heat estimation model can be used to calculate the heat exchanger between the thermal runaway cell and the air in the battery under test, as well as to calculate the internal thermal resistance of the thermal runaway cell, so as to measure the thermal diffusion performance of the thermal runaway cell based on these two calculations.

[0236] Optionally, the heat estimation model can be determined using the following relationship (1):

[0237]

[0238] Among them, ρ represents the density of the battery cell, C prepresents the specific heat capacity of the battery cell, T represents the temperature of the battery cell, τ represents the test time of the battery cell, represents the rate of change of temperature over time, k represents the thermal conductivity, Indicates the self-generated heat of the battery cell. The density of the battery cell, the specific heat of the battery cell, the self-generated heat of the battery cell, and the thermal conductivity are all attribute parameters of the battery cell, and the computer equipment can calculate the density of the battery cell and the specific heat of the battery cell based on some geometric parameters of the battery cell. For example, the density of the battery cell and the specific heat of the battery cell can be calculated based on the length of the battery cell, the width of the battery cell, the height of the battery cell, the thickness of the side shell of the battery cell, the thickness of the large shell of the battery cell, the thickness of the ground shell of the battery cell, etc. Optionally, the density of the battery cell, the specific heat of the battery cell, the thermal conductivity of the battery cell, and the self-generated heat of the battery cell can also be determined according to the description file of the battery cell.

[0239] In an embodiment of the present application, when the computer device obtains the property parameters of the battery to be tested based on the aforementioned steps, the user can trigger the generation of a test instruction on the test interface by clicking a control, voice input, or text input, and optionally, the test instruction can include an identifier of a heat estimation model. When the computer device responds to a test instruction triggered by the user on the test interface, the test instruction can be parsed, the identifier of the heat estimation model can be extracted therefrom, and the heat estimation model can be further searched from a database based on the identifier of the heat estimation model, and the property parameters of the battery to be tested are input into the heat estimation model for measurement, and the temperature change data of each surface on the thermal runaway cell in the battery to be tested is measured, that is, the test data is obtained.

[0240] The test method described in the embodiment of the present application obtains the property parameters of the battery to be tested by responding to the input instructions triggered by the user on the test interface, and responds to the test instructions triggered by the user on the test interface, inputs the property parameters into the heat estimation model for measurement, obtains the test data of the battery to be tested, and displays the test data on the test interface. The above test method provides a simulation application that can test the battery to be tested, that is, by inputting the corresponding test instructions on the test interface of the application, the thermal runaway condition or thermal runaway heat dissipation condition of the battery to be tested can be tested according to user needs and using a preset heat estimation model. Compared with the traditional method of testing the battery to be tested, the above method is a user-operable simulation test method that does not rely on the actual thermal runaway battery for testing, and can avoid the additional cost caused by design trial and error to a certain extent, and reduce the number of test experiments, thereby reducing the test cost of the battery to be tested and improving the test efficiency of the battery to be tested to a certain extent.

[0241] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0242] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be construed as limiting the scope of the patent application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent application shall be subject to the attached claims.

Claims

1. A battery, characterized in that: It includes a battery cell and a composite thermal insulation pad arranged on at least one side of the battery cell, the composite thermal insulation pad includes a first thermal insulation layer, a composite phase change layer and a second thermal insulation layer which are stacked, the composite phase change layer includes a phase change material layer and a packaging layer arranged on the outer peripheral side of the phase change material layer, the thickness of the composite phase change layer is 1mm to 4mm, and the thickness of the first thermal insulation layer and the second thermal insulation layer are each independently 1mm to 3mm.

2. The battery according to claim 1, characterized in that The battery satisfies at least one of the following conditions: (1) The thickness of the composite phase change layer is 1.5 mm to 3.5 mm; (2) The thickness of the first heat-insulating layer and the second heat-insulating layer are each independently 1 mm to 2.5 mm.

3. The battery according to claim 1, characterized in that The battery cell is a ternary lithium battery, the thickness of the composite phase change layer is 1.5 mm to 3.3 mm, and the thickness of the first heat insulation layer and the second heat insulation layer are independently 1 mm to 2.5 mm.

4. The battery according to claim 3, characterized in that The atomic ratio of nickel element in the ternary positive electrode material of the battery cell is greater than 0 and less than 50% of the ternary elements, and the thickness of the first thermal insulation layer and the second thermal insulation layer are independently 1 mm to 2 mm.

5. The battery according to claim 4, characterized in that The battery meets one of the following conditions: (1) The capacity of the battery cell is less than 120 Ah, the thickness of the composite phase change layer is 1.5 mm, and the thickness of the first thermal insulation layer and the second thermal insulation layer are independently 1 mm to 1.5 mm; (2) The capacity of the battery cell is ≥120Ah and <215Ah, the thickness of the composite phase change layer is 2.3mm, and the thickness of the first thermal insulation layer and the second thermal insulation layer are independently 1.5mm to 2mm; (3) The capacity of the battery cell is ≥215Ah and <260Ah, the thickness of the composite phase change layer is 3.3mm, and the thickness of the first thermal insulation layer and the second thermal insulation layer are independently 1.5mm to 2mm.

6. The battery according to claim 3, characterized in that The nickel element in the ternary positive electrode material in the battery cell accounts for ≥50% and <70% of the atoms of the ternary elements, the thickness of the composite phase change layer is 2.3mm-3.3mm, and the thickness of the first insulation layer and the second insulation layer are each independently 1.5mm-2.5mm.

7. The battery according to claim 6, characterized in that The battery meets one of the following conditions: (1) The capacity of the battery cell is less than 150 Ah, and the thickness of the first thermal insulation layer and the second thermal insulation layer are each independently 1.5 mm; (2) The capacity of the battery cell is ≥150Ah and <200Ah, and the thickness of the first thermal insulation layer and the second thermal insulation layer are independently 1.5 mm to 2 mm; (3) The capacity of the battery cell is ≥200 Ah and <260 Ah, and the thickness of the first thermal insulation layer and the second thermal insulation layer are independently 1.5 mm to 2.5 mm.

8. The battery according to claim 3, characterized in that The nickel element in the ternary positive electrode material in the battery cell accounts for ≥70% of the atoms of the ternary elements.

9. The battery according to claim 8, characterized in that The battery meets one of the following conditions: (1) The capacity of the battery cell is less than 100 Ah, the thickness of the composite phase change layer is 1.5 mm, and the thickness of the first thermal insulation layer and the second thermal insulation layer are independently 1 mm to 1.5 mm; (2) The capacity of the battery cell is ≥100Ah and <120Ah, the thickness of the composite phase change layer is 2.3mm-3.3mm, and the thickness of the first thermal insulation layer and the second thermal insulation layer are each independently 1mm-1.5mm; (3) The capacity of the battery cell is ≥120 Ah, the thickness of the composite phase change layer is 2.3 mm to 3.3 mm, and the thickness of the first thermal insulation layer and the second thermal insulation layer are each independently 2 mm to 2.5 mm.

10. The battery according to claim 1, characterized in that The battery cell is a lithium iron phosphate battery, the thickness of the composite phase change layer is 1.5 mm to 3.3 mm, and the thickness of the first heat insulation layer and the second heat insulation layer are each independently 1 mm to 2 mm.

11. The battery according to claim 10, characterized in that The battery meets one of the following conditions: (1) The capacity of the battery cell is less than 160 Ah, the thickness of the composite phase change layer is 1.5 mm, and the thickness of the first thermal insulation layer and the second thermal insulation layer are independently 1 mm to 1.5 mm; (2) The capacity of the battery cell is ≥160Ah and <260Ah, the thickness of the composite phase change layer is 1.5 mm to 2.3 mm, and the thickness of the first thermal insulation layer and the second thermal insulation layer are each independently 1 mm to 1.5 mm; (3) The capacity of the battery cell is ≥260Ah and <450Ah, the thickness of the composite phase change layer is 2.3 mm to 3.3 mm, and the thickness of the first thermal insulation layer and the second thermal insulation layer are each independently 1.5 mm to 2 mm.

12. The battery according to claim 1, characterized in that The battery cell is a sodium ion battery, the thickness of the composite phase change layer is 1.5 mm to 2.3 mm, and the thickness of the first heat insulation layer and the second heat insulation layer are each independently 1 mm to 2 mm.

13. The battery according to claim 12, characterized in that The battery meets one of the following conditions: (1) The capacity of the battery cell is less than 93 Ah, the thickness of the composite phase change layer is 1.5 mm, and the thickness of the first thermal insulation layer and the second thermal insulation layer are independently 1 mm to 1.5 mm; (2) The capacity of the battery cell is ≥93Ah and <117Ah, and the thickness of the first thermal insulation layer and the second thermal insulation layer are independently 1 mm to 1.5 mm; (3) The capacity of the battery cell is ≥117Ah and <180Ah, the thickness of the composite phase change layer is 1.5mm, and the thickness of the first thermal insulation layer and the second thermal insulation layer are independently 1.5mm to 2mm.

14. The battery according to any one of claims 1 to 13, characterized in that: There are multiple battery cells, and the composite thermal insulation pad is arranged between at least two adjacent battery cells.

15. The battery according to claim 14, characterized in that The composite heat-insulating pad is arranged between the large surfaces of two adjacent battery cells.

16. The battery according to any one of claims 1 to 13, characterized in that: The edges of the first heat-insulating layer and the second heat-insulating layer are connected to each other to form an assembly cavity, and the composite phase-change layer is located in the assembly cavity.

17. The battery according to claim 16, characterized in that An edge of at least one side surface of at least one of the first heat-insulating layer and the second heat-insulating layer forms a convex portion, and the convex portion encloses and forms at least a portion of the assembly cavity.

18. The battery according to any one of claims 1 to 13, characterized in that The composite thermal insulation pad also includes a first packaging frame and a second packaging frame. The first packaging frame is arranged on one side of the first thermal insulation layer, and the second packaging frame is arranged on one side of the second thermal insulation layer. The first packaging frame and the second packaging frame cooperate to fix the first thermal insulation layer, the composite phase change layer and the second thermal insulation layer.

19. The battery according to claim 18, characterized in that The first packaging frame has a first limiting groove, the second packaging frame has a second limiting groove, and the first thermal insulation layer, the composite phase change layer and the second thermal insulation layer are limited in a limiting space formed by the first limiting groove and the second limiting groove.

20. The battery according to any one of claims 1 to 13, characterized in that The composite thermal insulation pad meets at least one of the following conditions: (1) The composite thermal insulation pad further comprises a first adhesive layer and a second adhesive layer, wherein the first thermal insulation layer is connected to the encapsulation layer via the first adhesive layer, and the second thermal insulation layer is connected to the encapsulation layer via the second adhesive layer; (2) The composite thermal insulation pad further includes a release adhesive layer, the release adhesive layer includes a third adhesive layer and a release film, the third adhesive layer is arranged on the outer surface of the first thermal insulation layer and the second thermal insulation layer, and the release film is arranged on the outer surface of the third adhesive layer; (3) The first thermal insulation layer and the second thermal insulation layer are ceramic material layers; (4) The encapsulation layer is an aluminum-plastic film or a polymer encapsulation film; (5) The thickness of the packaging layer is 0.1 mm to 0.3 mm.

21. The battery according to any one of claims 1 to 13, characterized in that The battery cell includes a housing; the housing satisfies at least one of the following characteristics: (1) The wall thickness of the shell is 0.5 mm to 0.8 mm; (2) The housing is a rectangular housing; (3) The shell is an aluminum alloy shell.

22. The battery according to any one of claims 1 to 13, characterized in that The battery cell includes a shell, which is a rectangular shell with an opening. The opening direction of the shell is the height direction of the shell. The height of the shell is 80mm to 210mm, the length of the shell is 90mm to 240mm, and the width of the shell is 20mm to 80mm.

23. An electrical device, characterized in that: Comprising a battery as claimed in any one of claims 1 to 22.

Citation Information

Cited By

  • Battery pack

    CN120237341A

  • Battery device and electrical device

    WO2026193642A1